Property Improvement of α-Amylase from Bacillus stearothermophilus by Deletion of Amino Acid Residues Arginine 179 and Glycine 180 - Yuanming Gai; Jingqi Chen; Shibin Zhang; Beiwei Zhu; Dawei Zhang (Food Technology and Biotechnology, 2018)
To improve the properties of α-amylase from Bacillus stearothermophilus (AmyS), a deletion mutant AmyS∆R179-G180 was constructed by deleting arginine (Arg179) and glycine (Gly180) using site-directed mutagenesis. AmyS and AmyS∆R179-G180 were expressed in Bacillus subtilis and purified by ammonium sulfate precipitation, after which the enzymatic properties were characterized and compared. By deleting amino acids Arg179 and Gly180, the thermostability of α-amylase AmyS∆R179-G180 was enhanced and the half-life at 100 °C significantly increased from 24 to 33 min. In addition, AmyS∆R179-G180 exhibited greater acid resistance and lower calcium requirements to maintain α-amylase activity. The secretory capacity of the recombinant strain was evaluated by fed-batch fermentation in a 7.5-litre fermentor in which high α-amylase activity was obtained. The highest activity reached 3300 U/mL with a high productivity of 45.8 U/(mL•h).